Dampak media sosial terhadap pola pikir dan komunikasi remaja di Indonesia - ayu, putri aprilia rahma (Maliki Interdisciplinary Journal, 2026)
While social media undeniably marks technological progress that simplifies many aspects of life, its pervasive presence—especially among teenagers—carries worrying negative side effects on their mental health and behavior. This text highlights several serious threats that emerge from digital activity. Psychologically, social media fuels a ’confirmation bias,’ turning these teenagers into praise-seekers, attention-hungry individuals, and those constantly looking for validation from others. Furthermore, their reliance on screen-based interaction chips away at their real-world social skills. Consequently, they tend to become confused, awkward, or even afraid of face-to-face encounters, which greatly increases their risk of becoming anti-social, potentially leading to stress and depression. Another major concern frequently voiced by parents is that teens are becoming familiar with new words that are negative or vulgar. These dirty words are easily adopted out of sight, damaging etiquette and creating toxic friendship environments. On top of that, social media gives birth to a new form of harassment known as Cyberbullying. Examples like ’Trash Talk’ during online gaming are common. This digital harassment is extremely dangerous as it can destroy the self-confidence and emotional stability of vulnerable adolescents. And finally, the relentless advertising on social media also heavily influences purchasing behavior. Exposure to products increases brand awareness, leading to impulsive buying. What’s alarming is that when parents say no, some teenagers resort to stealing money or misusing their parents’ credit cards. This is a serious issue because it can instill the bad habit of theft early on. All these findings underscore the necessity for stricter parental supervision in this digital era.